1991
DOI: 10.1038/352818a0
|View full text |Cite
|
Sign up to set email alerts
|

Base pairing between U2 and U6 snRNAs is necessary for splicing of a mammalian pre-mRNA

Abstract: Splicing of pre-messenger RNA in eukaryotic cells occurs in a multicomponent complex termed the spliceosome, which contains small nuclear ribonucleoprotein particles (snRNPs), protein factors and substrate pre-mRNA. Assembly of the spliceosome involves the stepwise binding of snRNPs and protein factors to the pre-mRNA through a poorly understood mechanism which probably involves specific RNA-RNA, RNA-protein and protein-protein interactions. Of particular interest are the interactions between snRNPs, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 32 publications
6
112
0
1
Order By: Relevance
“…To examine the possible base pairing of snRNAs to the 59 splice site sequence of U12-dependent introns, a series of mutations of this sequence was constructed in the human nucleolar protein P120 intron F expression system+ This minigene construct contains exons 5-8 and introns E, F, and G of the gene driven from a CMV promoter (Hall & Padgett, 1996)+ Figure 2A shows the sequences of the 59 splice site of P120 intron F and the portions of U11 and U6atac snRNAs that are proposed to base pair to the 59 splice site+ Figure 2B shows the sequences of the P120 59 splice mutants and the compensating mutant snRNAs used in this work+ The numbering of the P120 and snRNA mutants shown in Figure 2B corresponds to the numbering of nucleotide positions in Figure 2A+ To test the effects of specific U6atac mutations on the in vivo activity of these 59 splice site mutants, a U6atac expression gene was constructed by inserting the coding sequence of U6atac (Tarn & Steitz, 1996b) into a U6 gene that had been previously shown to be active when transfected into cells (Wu & Manley, 1991)+ In vitro transcription of this construct in the presence of a-amanitin produced a band of approximately 126 nt, which is consistent with the production of U6atac RNA by RNA polymerase III (data not shown)+ Mutations were introduced into this construct that were designed to restore base pairing to the 59 splice site mutations (Fig+ 2A,B)+ The U11 snRNA mutants were described previously (Kolossova & Padgett, 1997) or were constructed as described in Materials and Methods+…”
Section: Mutants Of U6atac Suppress the Splicing Defect Of 59 Splice mentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the possible base pairing of snRNAs to the 59 splice site sequence of U12-dependent introns, a series of mutations of this sequence was constructed in the human nucleolar protein P120 intron F expression system+ This minigene construct contains exons 5-8 and introns E, F, and G of the gene driven from a CMV promoter (Hall & Padgett, 1996)+ Figure 2A shows the sequences of the 59 splice site of P120 intron F and the portions of U11 and U6atac snRNAs that are proposed to base pair to the 59 splice site+ Figure 2B shows the sequences of the P120 59 splice mutants and the compensating mutant snRNAs used in this work+ The numbering of the P120 and snRNA mutants shown in Figure 2B corresponds to the numbering of nucleotide positions in Figure 2A+ To test the effects of specific U6atac mutations on the in vivo activity of these 59 splice site mutants, a U6atac expression gene was constructed by inserting the coding sequence of U6atac (Tarn & Steitz, 1996b) into a U6 gene that had been previously shown to be active when transfected into cells (Wu & Manley, 1991)+ In vitro transcription of this construct in the presence of a-amanitin produced a band of approximately 126 nt, which is consistent with the production of U6atac RNA by RNA polymerase III (data not shown)+ Mutations were introduced into this construct that were designed to restore base pairing to the 59 splice site mutations (Fig+ 2A,B)+ The U11 snRNA mutants were described previously (Kolossova & Padgett, 1997) or were constructed as described in Materials and Methods+…”
Section: Mutants Of U6atac Suppress the Splicing Defect Of 59 Splice mentioning
confidence: 99%
“…The U6 coding region of a U6 snRNA gene (Wu & Manley, 1991; obtained from J+ Manley) was replaced with the U6atac sequence by PCR techniques+ First, the U6atac cDNA sequence from a U6atac plasmid (Tarn & Steitz, 1996b; obtained from J+ Steitz) was amplified using the primers TGTGGAAAGGACGAAACACCGTGTTGTATGAAAGGAG AGA (primer 1) and GCTCTAGAAAAACAACCTGATGTAA AAACAGAAAAACAACCTGATGTAAAAACGATGGTTAGAT GCCA (primer 2)+ This produced a DNA fragment with the 59 end of U6atac joined to the promoter-proximal region of the U6 snRNA gene and the 39 end of U6atac joined to the 39 downstream region of the U6 gene terminating in an Xba I restriction site+ Next, the upstream portion of the U6 snRNA gene from Ϫ328 to Ϫ1 was amplified using the primers CGGAATTCCCCAGTGGAAAGACGCGCA (primer 3) and TCTCTCCTTTCATACAACACGGTGTTTCGTCCTTTCC ACA (primer 4)+ This produced a DNA fragment with a 39 end complementary to the U6atac fragment and a 59 end with an EcoR 1 restriction site+ The two fragments were then combined and amplified with primers 2 and 3 to join the U6 snRNA upstream sequences to the U6atac cDNA sequences+ Finally, the resulting fragment was digested with EcoR 1 and Xba I and ligated into pALTER-1 (Promega)+ The correct structure was confirmed by sequencing+…”
Section: Construction Of U6atac Expression Plasmidmentioning
confidence: 99%
See 1 more Smart Citation
“…In the newly formed spliceosome, a specific sequence of U5 interacts with the exon sequences at the 5' and 3' splice sites (Newman and Norman, 1991;Newman and Norman, 1992;Wyatt et al, 1992;Cortes et al, 1993;Sontheimer and Steitz, 1993), and other sequences of U4 and U6 base-pair with each other. Then, before the first step of splicing occurs, the spliceosome undergoes dynamic changes, resulting in the departure of U1 and U4, and the formation of new duplexes, including those between U2 and U6, and between U6 and the 5' splice site (Hausner et al, 1990;Datta and Weiner, 1991;Wu and Manley, 1991;Yean and Lin, 1991;Madhani and Guthrie, 1992;Sawa and Abelson, 1992;Wassarman and Steitz, 1992;Lesser and Guthrie, 1993;Nilsen, 1994). The resulting conformational changes lead to the formation of the active spliceosome (complex B2), triggering the first step of splicing, where the bulged-out branch point adenosine nucleophilically attacks the phosphate at the 5' splice site.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that certain RNA species possess catalytic activity has generated significant interest in the potential therapeutic use of catalytic RNA molecules (ribozymes) in controlling gene expression (for a review, see Christoffersen & Marr, 1995)+ Ribozymes have been shown to function in trans and can be directed against foreign target sequences by flanking the catalytic core with sequences complementary to the target (Uhlenbeck, 1987;Haseloff & Gerlach, 1988)+ The hammerhead is the smallest of the known ribozyme motifs and therefore amenable to experimental manipulation (for a review, see Symons, 1992)+ Hammerhead ribozymes have broad potential as therapeutic agents for the selective control of gene expression (for a review, see Haseloff & Gerlach, 1988;Sarver et al+, 1990;Christoffersen & Marr, 1995)+ An important problem confronting the use of hammerhead ribozymes as therapeutic agents is that of maximizing the interaction of ribozymes to their target RNAs in vivo+ Experiments employing the unique property of retroviruses to dimerize prior to and during packaging have provided a paradigm for ribozyme-target colocalization (Sullenger & Cech, 1993;Pal et al+, 1998)+ The dimerization and packaging of retroviral RNAs creates a unique physical association of two genomic RNAs+ When a ribozyme is tethered to the dimerization domain, the physical interaction of two dimerization sequences facilitates the base pairing of ribozyme to target+ Physical associations of nonviral RNAs occur within cells, but these usually involve specific base pairing interactions such as snRNAs with splicing signals (Wu & Manley, 1991;Sun & Manley, 1995;Incorvaia & Padgett, 1998)+ The interaction of U1 snRNA with the 59 splice signal has been used as an approach for colocalization of a ribozyme with an HIV target (Michienzi et al+, 1998)+ More subtle methods for ribozyme-target colocalization can take advantage of the properties of some messenger RNAs to be localized within specific subcellular compartments+ The first evidence for cytoplasmic mRNA localization came from the observation that actin tran-scripts are unevenly distributed in ascidian embryos (Jeffery et al+, 1983)+ Subsequently, several maternal mRNAs were identified in Xenopus (Melton, 1987) and Drosophila (Frigerio et al+, 1986) that are localized during oogenesis, and many mRNAs are localized in neurons (Garner et al+, 1988;Burgin et al+, 1990;Tiedge et al+, 1991) and oligodendrocytes (Ainger et al+, 1993)+ Localized mRNAs have also been discovered in somatic cells …”
Section: Introductionmentioning
confidence: 99%